An Analytical Study of Contract Termination Options in Afghan Law - Aminullah Shayeq; Saifuddin Jahed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Contract termination options (Khiyarat) represent one of the most significant aspects of civil law, granting the contracting parties the legal right to unilaterally rescind a contract under specific and legally prescribed conditions. This legal mechanism is designed to uphold justice within contractual relations and to prevent potential harm resulting from misalignment between the contract's terms and the true intent or circumstances of the parties involved. The relevance of examining Khiyar in the legal system of Afghanistan has grown increasingly critical, particularly in light of ongoing legal reforms and the imperative to enhance legal certainty in civil contracts. The present article aims to provide a comprehensive and scholarly analysis of contract termination options as regulated under the Afghan Civil Code, with specific reference to the principles of Hanafi jurisprudence. By elucidating the various types of Khiyar, their conditions of applicability, legal consequences, and relevant judicial practice, this study identifies existing legislative gaps and proposes legal reforms to improve coherence and practical implementation. The research employs a descriptive-analytical methodology, relying on statutory sources, Islamic jurisprudential texts, and relevant legal scholarship. A comparative analysis is also conducted between Afghan legal provisions and the doctrines of classical Hanafi jurisprudence. Findings indicate that, despite the diverse and extensive presence of Khiyar provisions in Afghan law, ambiguities in definition and inconsistencies with Hanafi jurisprudence pose challenges to their uniform application. Accordingly, the article recommends targeted legal reforms to clarify key concepts and ensure the effective and harmonized enforcement of termination rights, thereby safeguarding contractual justice and enhancing the legal security of transactions.